The Mealtime Assessment Scale (MAS): Part 2 – Preliminary Psychometric Analysis - Pizzorni, Nicole; Valentini, Debora; Gilardone, Marco; Scarponi, Letizia; Tresoldi, Martina; Barozzi, Stefania; Corbo, Massimo; Schindler, Antonio (Folia phoniatrica et logopaedica, 2020)
Aims: The Mealtime Assessment Scale (MAS) was developed to assess swallowing safety and efficacy during the meal. The study aims to perform a preliminary validation of MAS by investigating internal consistency, inter-rater agreement, concurrent and known-group validity, and responsiveness. Methods:MAS was tested on 100 persons without dysphagia (group 1) and 100 persons with dysphagia (group 2). Fifty subjects were simultaneously evaluated at mealtime using MAS by two independent clinicians to test inter-rater agreement. For concurrent validity, MAS was correlated with the Mann Assessment of Swallowing Ability (MASA) and American Speech-Language-Hearing Association National Outcomes Measurement System (ASHA NOMS) swallowing scale. MAS scores of groups 1 and 2 were compared for known-group validity. Responsiveness was tested reassessing 36 patients from group 2 after diet improvement. Results: Internal consistency and responsiveness were established for efficacy but not for safety. For inter-rater agreement, an average deviation index <0.66 was found for all items. MAS showed strong correlations with MASA and ASHA NOMS. MAS scores were significantly different between groups 1 and 2. Conclusion:Preliminary evidence of the validity and reliability of MAS was established, except for the internal consistency and the responsiveness of the safety subscale. Further studies need to complete the validation process.